2009
DOI: 10.1128/aem.00457-09
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Mucus from the Coral Acropora palmata by the Pathogen Serratia marcescens and by Environmental and Coral Commensal Bacteria

Abstract: In recent years, diseases of corals caused by opportunistic pathogens have become widespread. How opportunistic pathogens establish on coral surfaces, interact with native microbiota, and cause disease is not yet clear. This study compared the utilization of coral mucus by coral-associated commensal bacteria ("Photobacterium mandapamensis" and Halomonas meridiana) and by opportunistic Serratia marcescens pathogens. S. marcescens PDL100 (a pathogen associated with white pox disease of Acroporid corals) grew to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…Consistent with this hypothesis, of all the tested coral and environmental bacteria, Serratia marcescens PDL100 reached the highest final population density when grown in vitro on mucus of Acropora palmata (Krediet et al 2009). This strain of S. marcescens was originally isolated as a cause of white pox, a rapidly progressing coral tissue necrosis of the threatened Caribbean coral A. palmata (Patterson et al 2002).…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Consistent with this hypothesis, of all the tested coral and environmental bacteria, Serratia marcescens PDL100 reached the highest final population density when grown in vitro on mucus of Acropora palmata (Krediet et al 2009). This strain of S. marcescens was originally isolated as a cause of white pox, a rapidly progressing coral tissue necrosis of the threatened Caribbean coral A. palmata (Patterson et al 2002).…”
Section: Introductionsupporting
confidence: 65%
“…This strain of S. marcescens was originally isolated as a cause of white pox, a rapidly progressing coral tissue necrosis of the threatened Caribbean coral A. palmata (Patterson et al 2002). The observations that the white pox strain was more efficient at utilizing mucus of the host coral in vitro suggested that this ability to efficiently degrade mucus may be linked to its pathogenicity (Krediet et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial receptors can bind to mucus (Rosenberg and Falkovitz, 2004;Kvennefors et al, 2008), and this directly controls the composition of the associated microbiota. The mucus polymer itself and small molecular weight compounds within it serve as both nutrient sources for the microbes and signals that modulate behavior and gene expression in the associated microbial communities (Vacelet and Thomassin, 1991;Wild et al, 2004;Ritchie, 2006;Sharon and Rosenberg, 2008;Krediet et al, 2009aKrediet et al, , 2009b. Although the fate of coral mucus in the reef environment and its role in coral-associated microbial communities are becoming more clear, significantly less is known about the microbe-microbe interactions within the coral surface mucus layer.…”
Section: Introductionmentioning
confidence: 99%
“…Coral mucus supports growth of bacteria up to 10 6 -10 8 cfu ml À 1 (Sharon and Rosenberg, 2008;Krediet et al, 2009b;Garren and Azam, 2010). Nutrients and chemicals from the host excreted with the mucus determine the composition and structure of the associated microbial communities (Ritchie, 2006;Garren and Azam, 2012).…”
Section: Introductionmentioning
confidence: 99%